Analyzing the Impact of Coffee Company’s Marketing Campaigns and Brand Awareness on Consumer Purchase Intention - Paul, Gadi Dung; A/P Perak Kerof, Chaleeda; Hui Xin, Ang; Binti Andek Mohd Yasin, Andek Farzana; Jingrui, Chen; Chauhan, Akanksha; Hee Song, Ng (AIBPM Publisher, 2024)
Starbucks, the largest coffeehouse chain, operates in 14 distinct markets across the Asia Pacific region, renowned for its diverse coffee and tea consumption cultures. Starbucks, an established company in the worldwide coffee sector, makes huge investments in creative marketing techniques to attract and keep consumers. Starbucks faces competition as consumers increasingly prefer locally sourced products and flavors. Our study investigates the primary impacts of Starbucks' marketing campaigns on consumer purchase intention in Malaysia and India. We are using quantitative surveys as part of our technique approach to collect detailed information on the perspectives and behaviors of consumers. Data were collected from 150 Starbucks customers through surveys. Our results indicate that Starbucks' marketing campaigns significantly influence consumer intention in these regions. Our findings highlight the importance of brand awareness and marketing campaigns in shaping consumer purchase intentions. Our study offers valuable insights for Starbucks to enhance the effectiveness of its marketing campaigns and boost consumer purchasing power.